Flexible composite electromagnetic shielding film
The flexible composite electromagnetic shielding membrane addresses the inadequacies of traditional materials by employing a layered structure with conductive and insulating layers, carbon nanotubes, and iron-magnetic powders to achieve enhanced shielding effectiveness across a broad frequency range, ensuring effective protection against electromagnetic interference.
Patent Information
- Application Number
- CN202411888969.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-28
AI Technical Summary
Traditional flexible electromagnetic shielding materials, such as aluminum and copper foil, fail to provide adequate protection against high-frequency electromagnetic interference due to limitations in thickness and weight, leading to insufficient shielding effectiveness, especially in the high-frequency range.
A flexible composite electromagnetic shielding membrane with a layered structure, comprising an earthed conductive membrane layer, a high-strength insulating carrier layer, a high-frequency shielding coating layer with a combination of single-walled and multi-walled carbon nanotubes, hard carbon micro-powder, and iron-magnetic powders, forming a three-dimensional conductive network and enhancing absorption and scattering of electromagnetic waves.
The solution achieves a shielding effectiveness of over 40dB across a wide frequency range (100MHz to 25GHz), significantly improving protection against both low and high-frequency electromagnetic interference while maintaining flexibility and reducing production costs.
Smart Images

Figure CN119730216A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electromagnetic shielding, and in particular relates to an electromagnetic shielding film with wide-band protection, high shielding efficiency and process flexibility. Background Art
[0002] With the popularization and application of power electronic products, the widespread existence of electromagnetic radiation sources such as various high-frequency transformers, variable-frequency motors, low-frequency to high-frequency controllers, electric vehicles, wireless communications, etc., medical equipment, data centers, high-frequency high-speed cables, and flexible printed circuits (FPC) and other power electronic products require the use of electromagnetic shielding protection with high reliability, wide bandwidth, and high electromagnetic shielding efficiency. Traditional flexible electromagnetic shielding protective film materials such as aluminum foil Mylar and copper foil Mylar are limited by their thickness. There are induced currents and secondary emissions for high-frequency electromagnetic wave incident interference sources. The protection of high-frequency bands can no longer meet the needs of high-quality electromagnetic shielding protection.
[0003] Chinese invention patent CN108676467A proposes an absorbing composition and a flexible patch absorbing material, which are composed of epoxy resin, nanocrystalline absorber, white carbon black, curing agent, coupling agent, catalyst, dispersant, defoaming agent and mixed solvent. The flexible patch absorbing material adopts a layered structure, which includes an absorbing coating formed by the absorbing composition, an adhesive layer, a conductive substrate layer, an adhesive layer and a glass paper layer from top to bottom. The absorbing composition mainly uses ferromagnetic hexagonal barium ferrite or carbonyl iron powder, and the conductive substrate uses nickel-plated conductive nylon fiber or silver-plated conductive nylon woven into a conductive cloth. The average vertical reflectivity of the product at 8-12GHZ is below -2dB, and it has a certain electromagnetic shielding protection function for military facilities such as weapons and equipment. The product mainly uses the magneto-induced loss effect of ferromagnetic materials, the protection bandwidth is insufficient, the protection function of the low frequency band is weak, and the protection of the higher frequency band is not enough.
[0004] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art and products, the present invention provides an electromagnetic shielding film product with wide-band protection, high shielding effectiveness and process flexibility. Summary of the invention
[0005] The present invention provides a flexible composite electromagnetic shielding film, characterized in that the flexible composite electromagnetic shielding film adopts a layered composite structure, including the following functional film layers:
[0006] The electronic good conductor film layer A with grounding function and focusing on medium and low frequency electromagnetic shielding adopts rolled aluminum foil and / or electrolytic copper foil and / or rolled copper foil with a thickness of 5-25 microns; aluminum foil and copper foil have good conductivity, excellent reflection performance for low-frequency electromagnetic waves, and a certain ability to conduct the induced current generated by medium and high frequency electromagnetic waves through grounding; however, due to the thickness and weight of aluminum foil and copper foil, their electromagnetic shielding protection function corresponding to the medium and high frequency bands is still insufficient;
[0007] The insulating carrier film layer B with high mechanical strength adopts a biaxially oriented polyester film and / or an ultra-high molecular weight polyethylene microporous film with a thickness between 5-25 microns and a tensile strength greater than 120 MPa; in order to adapt to the process requirements of high-speed winding equipment and the high requirements of thicker shielding coatings for interface bonding strength, the present invention more preferably uses an ultra-high molecular weight polyethylene microporous film as a carrier.
[0008] A composite electromagnetic shielding coating C focusing on high-frequency protection is coated on one or both sides of the above-mentioned film layer A or film layer B. The thickness of the composite electromagnetic shielding coating C is between 30 and 600 microns, and the porosity of the composite electromagnetic shielding coating C is between 15 and 45%. The composite electromagnetic shielding coating C includes the following materials: single-walled carbon nanotubes C1, with a weight percentage of 0.10-0.40%, a length of the single-walled carbon nanotube greater than 100 microns, a tube diameter of 1.2-5 nanometers, and Ig / Id greater than 30. The single-walled carbon nanotubes with the above-mentioned technical characteristics have material properties close to those of perfect graphene winding materials, have excellent conductivity and very high mechanical strength, and a large aspect ratio characteristic brings about a high winding density; multi-walled carbon nanotubes C2, with a weight percentage of 0.40-4.00%, and a length of the multi-walled carbon nanotubes less than 90 microns , the tube diameter is less than 50 nanometers, and Ig / Id is less than 3. The multi-walled carbon nanotubes with the above technical characteristics have complementary functions with the long single-walled carbon nanotubes. The multi-walled carbon nanotubes are slightly shorter in length and slightly larger in diameter. The degree of graphitization and conductivity are lower than those of the single-arm carbon nanotubes. When used in combination with the above-mentioned single-arm carbon nanotubes, the dispersion uniformity of the liquid-solid slurry is greatly improved. After the combination of the two carbon nanotubes, they are entangled with other functional powder materials in the electromagnetic shielding coating to construct a three-dimensional conductive network; in addition, multi-walled carbon nanotubes naturally have interlayer physical interfaces, which can form n multiple reflections at the interface for the incidence and refraction of electromagnetic waves, and easily realize the scattering and absorption of electromagnetic waves; hard carbon micropowder C3, the weight percentage is between 55-95%, and the hard carbon micropowder C3 has the following technical characteristics: carbon content is greater than 99%, and density is between 1.50-1.75g / cm 3The average particle size D50 is between 3 and 16 microns, Ig / Id is less than 1.5, and the full width at half maximum (FWHM) of the XRD diffraction spectrum corresponding to the d002 diffraction peak is greater than or equal to 3°. The hard carbon micropowder with the above technical characteristics has a conductivity slightly inferior to that of graphite powder. The physical structure characteristic of the hard carbon powder C3 is that there are numerous nano-scale micropores inside. A single powder is composed of numerous SP2-bonded graphene sheets that are twisted and entangled with each other. At the same time, the amorphous carbon in the entangled area has many SP3 bonds. The special heterogeneous intrinsic structure of the hard carbon micropowder C3 naturally forms impedance matching and dielectric loss required for electromagnetic wave absorption that are superior to conventional polycrystalline materials, and electromagnetic When the wave propagates between the hard carbon powders and inside the powders, there are N multiple reflections / refractions, forming the characteristics of diffuse scattering and strong absorption. Even for shorter wavelength and ultra-high frequency X-rays, the intrinsic structure of the hard carbon powder can also form diffuse scattering and strong absorption characteristics. Therefore, the present invention adopts an electromagnetic shielding coating based on hard carbon as the main material, which has better high-frequency electromagnetic wave shielding performance; ferromagnetic material submicron powder C4, with a weight percentage of 5-45%, an average particle size D50 less than 1 micron, including ferrite, carbonyl iron powder, carbonyl nickel powder, iron-based MOF, nickel-based MOF, iron-nickel bimetallic MOF or a combination thereof, and the ferromagnetic submicron powder C4 has good magnetic The invention discloses a water-soluble polymer adhesive C5, wherein the weight percentage of the water-soluble polymer adhesive C5 is between 0.50% and 3.0%, and the water-soluble polymer adhesive C5 has a molecular weight greater than 150,000 and a melting point greater than or equal to 125°C, ... The structure provides suitable cohesive strength for the electromagnetic shielding coating. When coating, water-based slurry is used instead of organic solvent to prepare the slurry. After drying, the shielding coating is formed, which has the characteristics of low manufacturing cost and safe production; Surfactant C6, the weight percentage is between 0.10-0.50%, and one or a combination of fatty alcohol polyoxyethylene ether, polyoxyethylene-polyoxypropylene copolymer, low molecular weight polyvinyl pyrrolidone, and sodium dodecylbenzene sulfonate is used. The surfactant helps the wetting of the above-mentioned hard carbon micropowder and ferromagnetic submicron powder with the water-based slurry and carbon nanotubes, which is beneficial to the uniform dispersion of the liquid-solid slurry and the uniformity of coating; Nano rubber C7, the weight percentage is between 0.50-3.00%, glass transition temperature Tg is lower than -20℃, nano rubber C7 uses rubber latex as raw material, the particle size of nano rubber particles in the rubber latex is less than 500 nanometers, the rubber latex raw material uses one or a combination of styrene-butadiene rubber latex, nitrile rubber latex, polyacrylate latex, butadiene rubber latex, ethylene-propylene rubber latex, isoprene rubber latex, and the above rubber latex is used as the source of nano rubber. After the liquid-solid slurry is evenly dispersed, after the coating is dried, many nano rubber lattice buffer materials can be formed on the surface of the above micron-level hard carbon powder and submicron-level ferromagnetic powder, which can help the flexibility of the electromagnetic shielding coating, especially the thicker coating;.
[0009] The film layer D has an adhesive function, and the film layer D is a pressure-sensitive adhesive dot matrix or a continuous film layer, or a hot-melt adhesive dot matrix or a continuous film layer, and has a thickness of 1-5 microns, and is coated on the surface of the composite electromagnetic shielding coating C or the surface of the above other film layers;
[0010] The flexible composite electromagnetic shielding film adopts a layered composite structure, including but not limited to the following combinations: A / C / D / B / D, A / D / C / A / C / D, A / D / B / C / D, A / C / D, A / D / A / C / D, B / D / C / A / C / D, B / D / A / C / D, B / D / C / A / C / D, B / D / C / A / D, B / D / A / C / D / A / C / D;
[0011] In the test frequency range between 100MHZ and 25GHZ, the absolute value of the shielding effectiveness SE of the flexible composite electromagnetic shielding film is greater than 40dB. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a schematic diagram of the structure of a flexible composite electromagnetic shielding film of the present invention, wherein B is a PET polyester film, D is an EAA hot melt adhesive film layer, A is an aluminum foil or a copper foil, and C is an electromagnetic shielding coating. 1 and 4 in the schematic diagram represent electromagnetic wave absorbing functional powders composed of hard carbon micropowder and ferromagnetic submicron powder and nano rubber, and 2 and 3 represent a three-dimensional conductive network composed of single-arm carbon nanotubes and multi-walled carbon nanotubes and / or an interpenetrating network composed of a water-based polymer adhesive.
[0013] Figure 2 The XRD test spectrum of the hard carbon micropowder used in the present invention has a d002 diffraction peak with a full width at half maximum (FWHM) of about 5°, which has significant diffuse scattering characteristics for short-wavelength ultra-high frequency electromagnetic waves such as X-rays; compared with the XRD spectrum of traditional graphite powder, the full width at half maximum (FWHM) of its d002 diffraction peak is generally less than 1°. Traditional graphite powder has a higher degree of crystallinity and a typical reflection coherent diffraction enhancement effect, and its d002 diffraction peak presents a fine and tall sharp batch shape.
[0014] Figure 3 This is the Raman spectrum test spectrum of the hard carbon micropowder used in the present invention. A 532-nanometer laser is used as the radiation source. There are two obvious scattering peaks at about 1355 cm-1 (for the D band) and about 1590 cm-1 (corresponding to the G band). The scattering peak intensity ratio Ig / Id of the G band and the D band is less than 1. DETAILED DESCRIPTION
[0015] The invention is further described below in conjunction with embodiments, and the protection scope of the present invention is not limited to the following:
[0016] Embodiment 1: The flexible composite electromagnetic shielding film adopts a layered composite structure, including the following functional film layers: an electronic good conductor film layer A having a grounding function and focusing on medium and low frequency electromagnetic shielding, using an electrolytic copper foil with a thickness of 14-16 microns;
[0017] The insulating carrier membrane layer B with high mechanical strength is made of a 16-micron-thick biaxially oriented ultra-high molecular weight polyethylene microporous membrane, with a longitudinal and transverse tensile strength greater than 150 MPa, a porosity of 35-45%, and a pore size of about 50 nanometers;
[0018] The composite electromagnetic shielding coating C focusing on high-frequency protection is coated on both sides of the above-mentioned film layer A. The thickness of the single-sided coating of the composite electromagnetic shielding coating C is between 90-95 microns, and the porosity of the composite electromagnetic shielding coating C is between 25-37%. The composite electromagnetic shielding coating C includes the following materials: single-walled carbon nanotubes C1, with a weight percentage of 0.20-0.25%, a length of the single-walled carbon nanotube greater than 190 microns, a tube diameter of 1.5-3 nanometers, and an Ig / Id greater than 60; multi-walled carbon nanotubes C2, with a weight percentage of 1.20-1.30%, a length of the multi-walled carbon nanotube less than 80 microns, a tube diameter less than 20 nanometers, and an Ig / Id less than 1; hard carbon micropowder C3, with a weight percentage of 70-75%, and the hard carbon micropowder C3 has the following technical characteristics: a carbon content greater than 99%, a density between 1.60-1.65 g / cm 3, average particle size D50 is between 8 and 12 microns, Ig / Id is less than 1, and the full width at half maximum (FWHM) of the XRD diffraction spectrum corresponding to the d002 diffraction peak is close to 5°; ferromagnetic material submicron powder C4, weight percentage is between 20-25%, average particle size D50 is less than 0.5 micron, and carbonyl iron powder is used; water-soluble polymer adhesive C5, weight percentage is between 1.5-1.6%, and a composition of hydroxypropyl methylcellulose HPMC with a molecular weight greater than 200,000 and polyacrylic acid PAA is used; surfactant C6, weight percentage is between 0.20-0.30%, and polyoxyethylene-polyoxypropylene copolymer is used; nano rubber C7, weight percentage is between 1.9-2.0%, glass transition temperature Tg is lower than -40°C, nano rubber C7 uses rubber latex as raw material, the particle size of nano rubber particles in the rubber latex is less than 300 nanometers, and the rubber latex raw material uses polyacrylate emulsion;
[0019] The film layer D having an adhesive function is coated by dot-matrix gravure coating of a pressure-sensitive adhesive with a thickness of 2-4 microns and is coated on the surface of the composite electromagnetic shielding coating C or the surface of the other film layers mentioned above;
[0020] The layered composite structure of the flexible composite electromagnetic shielding film is as follows: B / D / C / A / C / D; in the test frequency range of 100MHZ to 25GHZ, the absolute value of the shielding effectiveness SE of the flexible composite electromagnetic shielding film is greater than 50dB.
Claims
1. A flexible composite electromagnetic shielding film, characterized in that: The flexible composite electromagnetic shielding film adopts a layered composite structure, including the following functional film layers: The electronic good conductor film layer A has a grounding function and focuses on medium and low frequency electromagnetic shielding, and adopts a rolled aluminum foil and / or an electrolytic copper foil and / or a rolled copper foil with a thickness of 5-25 microns; The insulating carrier film layer B with high mechanical strength is made of biaxially oriented polyester film and / or ultra-high molecular weight polyethylene microporous film with a thickness of 5-25 microns and a tensile strength of more than 120 MPa; The composite electromagnetic shielding coating C focusing on high-frequency protection is coated on one or both sides of the above-mentioned film layer A or film layer B. The thickness of the composite electromagnetic shielding coating C is between 30-600 microns, and the porosity of the composite electromagnetic shielding coating C is between 15-45%. The composite electromagnetic shielding coating C includes the following materials: single-walled carbon nanotubes C1, with a weight percentage of 0.10-0.40%, a length of the single-walled carbon nanotube greater than 100 microns, a tube diameter of 1.2-5 nanometers, and an Ig / Id greater than 30; multi-walled carbon nanotubes C2, with a weight percentage of 0.40-4.00%, a length of the multi-walled carbon nanotube less than 90 microns, a tube diameter less than 50 nanometers, and an Ig / Id less than 3; hard carbon micropowder C3, with a weight percentage of 55-95%, and the hard carbon micropowder C3 has the following technical characteristics: a carbon content greater than 99%, a density between 1.50-1.75 g / cm 3 , average particle size D50 is between 3 and 16 microns, Ig / Id is less than 1.5, and the full width at half maximum (FWHM) of the XRD diffraction spectrum corresponding to the d002 diffraction peak is greater than or equal to 3°; ferromagnetic material submicron powder C4, weight percentage is between 5 and 45%, average particle size D50 is less than 1 micron, including ferrite, carbonyl iron powder, carbonyl nickel powder, iron-based MOF, nickel-based MOF, iron-nickel bimetallic MOF or a combination thereof; water-soluble polymer adhesive C5, weight percentage is between 0.50 and 3.0%, using a water-soluble polymer with a molecular weight greater than 150,000 and a melting point greater than or equal to 125°C, including hydroxypropyl methylcellulose HPMC, sodium carboxymethyl cellulose CMC, hydroxyethyl cellulose HEC, polyvinyl alcohol PVA , one or a combination of polyacrylic acid PAA and polyvinyl pyrrolidone PVB; surfactant C6, with a weight percentage of 0.10-0.50%, using one or a combination of fatty alcohol polyoxyethylene ether, polyoxyethylene-polyoxypropylene copolymer, low molecular weight polyvinyl pyrrolidone, and sodium dodecylbenzene sulfonate; nano rubber C7, with a weight percentage of 0.50-3.00%, and a glass transition temperature Tg lower than -20°C, nano rubber C7 uses rubber latex as a raw material, and the particle size of the nano rubber particles in the rubber latex is less than 500 nanometers, and the rubber latex raw material uses one or a combination of styrene-butadiene rubber latex, nitrile rubber latex, polyacrylate emulsion, butadiene rubber latex, ethylene-propylene rubber latex, and isoprene rubber latex; The film layer D has an adhesive function, and the film layer D is a pressure-sensitive adhesive dot matrix or a continuous film layer, or a hot-melt adhesive dot matrix or a continuous film layer, and has a thickness of 1-5 microns, and is coated on the surface of the composite electromagnetic shielding coating C or the surface of the above other film layers; The flexible composite electromagnetic shielding film adopts a layered composite structure, including but not limited to the following combinations: A / C / D / B / D, A / D / C / A / C / D, A / D / B / C / D, A / C / D, A / D / A / C / D, B / D / C / A / C / D, B / D / A / C / D, B / D / ℃ / A / D, B / D / A / C / D / A / C / D; In the test frequency range between 100MHZ and 25GHZ, the absolute value of the shielding effectiveness SE of the flexible composite electromagnetic shielding film is greater than 40dB.
Citation Information
Patent Citations
Microwave absorbing composition and flexible-paster microwave absorbing material
CN108676467A
Cited By
Method for preparing high-permeability iron-nickel / iron-silicon magnetic powder core through lamination
CN120453046A